Optimized method for evaluation of bile acids from dry or ethanol preserved fecal samples as a tool for the identification of wild carnivores - Salame-Méndez, Arturo; Andrade-Herrera, Moisés; Zamora-Torres, Leo; Serrano, Héctor; Soto-Mendoza, Saúl; Castro-Campillo, Alondra; Ramírez Pulido, José; Haro-Castellanos, Jorge (Instituto de Ecología, A.C., 2012)
We optimize several aspects involved in the method for a reliable, more simple, and easy obtaining of bile acids (AB) and cholesterol (Co) from the feces of wild carnivores, including: selection of the optimal developer; adaptation of the mobile phase in a first chromatographic evaluation; optimization of separation through a second chromatographic evaluation with another mobile phase; the use of minimal amounts of both fecal sample (mg) or the ethanolic solution (uL) in which the former were preserved. The new procedure is simpler and easily reproducible, and thus it turns out to be an analytic, non-invasive, and feasible tool for the identification of wild carnivores by means of the AB within their feces. In order to probe the method, we analyzed feces from Puma concolor, Panthera onca, Canis lupus baileyi, and Canis latrans maintained in captivity, which are also described and, therefore, we also present for the first time, the profile of AB for the Mexican wolf.